2016
DOI: 10.1111/cei.12883
|View full text |Cite
|
Sign up to set email alerts
|

DUSP23 is over-expressed and linked to the expression of DNMTs in CD4+ T cells from systemic lupus erythematosus patients

Abstract: We evaluated the transcriptional expression of dual-specificity protein phosphatase 23 (DUSP23) in CD4 T cells from 30 systemic lupus erythematosus (SLE) patients and 30 healthy controls. DUSP23 mRNA levels were considerably higher in the patient group: 1490 ± 1713 versus 294·1 ± 204·2. No association was found between DUSP23 mRNA expression and the presence of typical serological and clinical parameters associated with SLE. Meaningful statistical values were obtained in the patient group between the levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Thus, it seems that this protein is relevant in controlling T cell responses in order to prevent autoimmune diseases. Interestingly, overexpression of DUSP23 in CD4 T cells of patients with systemic lupus erythematosus has been described [46]. The upregulation of DUSP22 and DUSP23 found in our work by Th1-polarising conditions suggests a regulatory role of these enzymes during T helper polarisation and, consequently, their contribution to the control or development of pathological polarisation should be investigated.…”
Section: Conclusion: Perspective On Autoimmune Diseasessupporting
confidence: 49%
“…Thus, it seems that this protein is relevant in controlling T cell responses in order to prevent autoimmune diseases. Interestingly, overexpression of DUSP23 in CD4 T cells of patients with systemic lupus erythematosus has been described [46]. The upregulation of DUSP22 and DUSP23 found in our work by Th1-polarising conditions suggests a regulatory role of these enzymes during T helper polarisation and, consequently, their contribution to the control or development of pathological polarisation should be investigated.…”
Section: Conclusion: Perspective On Autoimmune Diseasessupporting
confidence: 49%
“…Several studies reported that DUSPs also regulate immune-cell responses [23,73,74,75,76]. DUSP2, DUSP4, DUSP7, DUSP10, DUSP12, DUSP22, and DUSP23 are involved in human autoimmune diseases, including SLE [77,78,79,80,81] (Figure 3).…”
Section: Dusp Family Phosphatases Are Involved In T-cell Activatiomentioning
confidence: 99%
“…Dual-specificity protein phosphatase 23 (DUSP23) activates the IFN and IL pathways via dephosphorylation (17), and these pathways are responsible for the formation of NETs, which are sources of cfDNA (17, 18, 57). DUSP3, DUSP22, and VH1 participate in both the IL and IFN signaling pathways mainly by dephosphorylating signal transducer and activator of transcription (STAT) proteins (37, 38).…”
Section: Discussionmentioning
confidence: 99%
“…High IFN-α activity is frequently detected in sera from SLE patients (39). Moreover, patients with SLE exhibit a particular mRNA expression profile of IFN-dependent genes in leucocytes known as the IFN signature (17, 40, 41).…”
Section: Discussionmentioning
confidence: 99%